Impact and damage resistance studies on thermoplastic reinforced composites - Muhammad Shah Abdullah (Nanyang Technological University, 2021)
Composites are a well-known material and are widely used in the industries because of their desirable strength to weight ratio. However, there were two major concerns impact and damage tolerance. These could significantly diminish the strength of composites, without being visually detectable. Nowadays, thermoplastic matrices are being preferred over thermoset polymers, due to their toughness, recyclability, and reusability. In this study, thermoplastic is used as both fibre reinforcement and polymer matrix in a composite laminate. The results produced by mechanical testing will then determine if the use of thermoplastic fibre reinforcement, eventually increase the impact resistance of the composite laminate. This study also focuses on identifying the suitable fabricating parameters to produce specimens for mechanical testing, since there are no standard procedures on fabricating this type of composite laminates yet. The suitable fabricating parameters for a fully thermoplastic composite laminate was determined. The major parameters identified was hot press pressure and temperature. The application of pressure was elevated slowly to the desired value of 4.2MPa. Therefore, allowing better fibre impregnation, leading to higher density and lower void volume content. The concluded temperature for the hot press was 200°C. The threshold impact energy level for the composites used in this study is 57J. Impact damages resisted produced only light dents. However, at higher energy level of 64 and 70J, delamination and fibre failure were observed on the non-impacted side of the laminate, producing a straight line fracture or a cross-shaped fracture. The composite laminates perform better at lower strain rate of 1.2mm/min compared to 2mm/min, where higher average peak force and displacement was observed. This was mainly due to the large plastic deformation that occurred at a lower strain rate. The main mode of damage was cross shaped yarn sliding, which could be seen in all specimens. Nonetheless, the fully thermoplastic composite laminate performs better than thermosetting composites in terms of damage resistivity, ductility, and plastic deformation capabilities.